Mechanisms underlying TNFα‐induced enhancement of force generation in airway smooth muscle. Issue 17 (11th September 2019) - Sieck, Gary C.; Dogan, Murat; Young‐Soo, Han; Osorio Valencia, Sara; Delmotte, Philippe
Abstract: Airway diseases such as asthma are triggered by inflammation and mediated by proinflammatory cytokines such as tumor necrosis factor alpha (TNFα). Our goal was to systematically examine the potential mechanisms underlying the effect of TNFα on airway smooth muscle (ASM) contractility. Porcine ASM strips were incubated for 24 h with and without TNFα. Exposure to TNFα increased maximum ASM force in response to acetylcholine (Ach), with an increase in ACh sensitivity (hyperreactivity), as reflected by a leftward shift in the dose–response curve (EC50 ). At the EC50, the [Ca 2+ ]cyt response to ACh was similar between TNFα and control ASM, while force increased; thus, Ca 2+ sensitivity appeared to increase. Exposure to TNFα increased the basal level of regulatory myosin light chain (rMLC) phosphorylation in ASM; however, the ACh‐dependent increase in rMLC phosphorylation was blunted by TNFα with no difference in the extent of rMLC phosphorylation at the EC50 ACh concentration. In TNFα‐treated ASM, total actin and myosin heavy chain concentrations increased. TNFα exposure also enhanced the ACh‐dependent polymerization of G‐ to F‐actin. The results of this study confirm TNFα‐induced hyperreactivity to ACh in porcine ASM. We conclude that the TNFα‐induced increase in ASM force, cannot be attributed to an enhanced [Ca 2+ ]cyt response or to an increase in rMLC phosphorylation. Instead, TNFα increases Ca 2+ sensitivity of ASM force generation due to increased contractile protein content (greater number of contractile units) and enhanced cytoskeletal remodeling (actin polymerization) resulting in increased tethering of contractile elements to the cortical cytoskeleton and force translation to the extracellular matrix. Abstract : The tumor necrosis factor alpha (TNFα)‐induced increase in airway smooth muscle (ASM) force cannot be attributed to an enhanced [Ca 2+ ]cyt response or to an increase in regulatory myosin light chain phosphorylation. Instead, TNFα increases Ca 2+ sensitivity of ASM force generation due to increased contractile protein content and enhanced cytoskeletal remodeling resulting in increased tethering of contractile elements to the plasma membrane and force translation to the extracellular matrix.